The Effect Of Balance Leaf Boiling On Changes In High Blood Pressure In Menopause Women - Nani Yustina; Rosyidah Alfitri (Jurnal Maternitas Kebidanan, 2026)
Hypertension is a common health problem experienced by menopausal women due to decreasing estrogen levels, which affects cardiovascular function. One non-pharmacological therapy that can be used to help lower blood pressure is bay leaf decoction (Syzygium polyanthum). This study aims to determine the effect of bay leaf decoction on changes in high blood pressure in menopausal women at the Singosari Community Health Center. The study used a quantitative method with a quasi-experimental design using a one-group pretest-posttest design. The study sample consisted of 20 menopausal women with hypertension selected using a purposive sampling technique. Blood pressure measurements were taken before and after administration of bay leaf decoction. The data were analyzed using statistical tests with a significance level of α = 0.05. The results showed changes in blood pressure after administration of bay leaf decoction. The statistical test results obtained a p-value of 0.000 (p < 0.05), indicating that bay leaf decoction has an effect on changes in high blood pressure in menopausal women. It was concluded that bay leaf decoction is effective as a non-pharmacological therapy in helping to lower blood pressure in menopausal women.